Feeding behavior of the cirratulid Cirriformia filigera (Delle Chiaje, 1825) (Annelida: Polychaeta) - Pardo,E. V. (2004)
Observations of the feeding behavior of Cirriformia filigera (Delle Chiaje, 1825) (Annelida: Polychaeta) from the intertidal zone of São Francisco and Engenho D'água beaches (São Sebastião, State of São Paulo) were made in the laboratory. This species, like other cirratulids, is a deposit feeder, feeding mainly on sediment surface with the aid of its grooved and ciliated palps, which are used to capture food particles. The worm lies just beneath the substrate surface in a J-shaped tube. When feeding, it extends up to 4 palps over the sediment surface, capturing food particles which pass down the groove of each palp directly to the mouth. Only fine sand grains are ingested. The worm frequently extends 4 branchial filaments into the overlying water for aeration. When it moves with the prostomium sideways, it collects and transports sand grains that pass backwards along its ventral region until reaching the middle part of its body. Next, the parapodia and palps move the sand grains to the dorsal posterior end of the animal, covering this area with sand. Some sand grains are also ingested as the worm moves.